Resin composition and resin precoated sand

By using characteristic lignin-modified phenolic resins and additives, the problem of insufficient mechanical strength and expansion in resin-coated sand is solved, and resin-coated sand with high mechanical strength and low expansion is achieved, reducing the generation of tar and smoke and dust .

CN119233870APending Publication Date: 2024-12-31SUMITOMO BAKELITE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039993.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-16
Filing Date
2023-05-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

There is room for improvement in the existing lignin phenolic resins in terms of mechanical strength and expansion, especially in the application of resin-coated sand.

Method used

By using lignin-modified phenolic varnish-type phenolic resin with reduced free phenol content, a resin composition with high mechanical strength and low expansion is prepared, and a specific number average molecular weight, weight average molecular weight and lignin modification rate is combined. On the basis of this, lubricant and silane coupling agent are added to form a binder suitable as resin coated sand.

Benefits of technology

The high mechanical strength and low expansion properties of resin-coated sand are achieved, the generation of tar and smoke is reduced, and the strength and adhesion resistance of the casting mold are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129974910000061
    Figure BDA0005129974910000061
  • Figure BDA0005129974910000201
    Figure BDA0005129974910000201
Patent Text Reader

Abstract

A resin composition for resin-coated sand, the resin composition containing a lignin-modified novolac-type phenolic resin, the content of free phenols in the lignin-modified novolac-type phenolic resin being 2 mass% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition for producing resin-coated sand for shell molds, and resin-coated sand obtained by using the resin composition. Background Art

[0002] In the prior art, resin coated sand (RCS) is used as a material for shell mold casting used in the shell mold method. Resin coated sand is a material in which a resin layer as a binder is coated on the surface of sand or ceramic as an aggregate. As the resin layer of the resin coated sand, phenolic resin is generally used.

[0003] In recent years, from the viewpoint of suppressing environmental damage, it has been proposed to use raw materials derived from biomass that are suitable for carbon neutralization in phenolic resin used as a binder for resin-coated sand. For example, Patent Document 1 describes that in resin-coated sand containing biomass-derived resin and aggregate, a lignin-modified novolac-type phenolic resin obtained by reacting acid-modified lignin, phenols, and aldehydes is used as a biomass-derived resin. Patent Document 1 describes that a lignin-modified novolac-type phenolic resin obtained by using carboxylic acid-modified lignin or acetic acid-modified lignin is suitable for carbon neutralization and has excellent flexural strength and flexibility.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 6825925 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] However, the inventors of the present invention have found through research that the lignin phenol resin described in Patent Document 1 has room for improvement in terms of mechanical strength and expansion properties.

[0009] Means for solving technical problems

[0010] The present invention has been made in view of the above problems, and has been made by finding that a resin composition suitable for use as a binder for resin-coated sand can be obtained by using a lignin-modified novolac-type phenolic resin having a reduced free phenol content, which has high mechanical strength and low expansion.

[0011] According to the present invention, there are provided the following resin composition and resin-coated sand.

[0012] [1] A resin composition for resin-coated sand, wherein:

[0013] The resin composition contains a lignin-modified novolac-type phenolic resin.

[0014] The content of free phenols in the lignin-modified novolac-type phenolic resin is 2% by mass or less.

[0015] [2] The resin composition according to item [1], wherein the lignin-modified novolac-type phenolic resin is a novolac-type phenolic resin obtained by reacting lignin, phenols and aldehydes in the presence of an acid catalyst.

[0016] [3] The resin composition according to item [1] or [2], wherein the number average molecular weight of the lignin-modified novolac-type phenolic resin is 300 or more and 1500 or less.

[0017] [4] The resin composition according to item [2], wherein the weight average molecular weight of the lignin is 2,000 to 100,000.

[0018] [5] The resin composition according to any one of items [1] to [4], wherein the softening point of the lignin-modified novolac-type phenolic resin is 70° C. or higher and 105° C. or lower.

[0019] [6] The resin composition according to any one of items [1] to [5], wherein the lignin modification rate of the lignin-modified novolac-type phenolic resin is 10% to 50%.

[0020] [7] The resin composition according to any one of items [1] to [6], further comprising a lubricant.

[0021] [8] The resin composition according to item [7], wherein the lubricant contains an amide compound.

[0022] [9] The resin composition according to any one of items [1] to [8], further comprising a silane coupling agent.

[0023]

[10] The resin composition according to item [9], wherein the silane coupling agent comprises an aminosilane coupling agent.

[0024]

[11] Resin-coated sand comprising aggregate, a lubricant, and the resin composition according to any one of items [1] to

[10] .

[0025]

[12] The resin-coated sand according to item

[11] , further comprising a silane coupling agent.

[0026]

[13] The resin-coated sand according to item

[11] or

[12] , wherein the aggregate is coated with a resin layer formed from the resin composition.

[0027] Effects of the Invention

[0028] According to the present invention, a resin composition and resin-coated sand are provided. The cured product of the resin composition has excellent mechanical strength and low expansion, and is suitable for use as a binder for the resin-coated sand. DETAILED DESCRIPTION

[0029] Hereinafter, embodiments of the present invention will be described.

[0030] [Resin composition for resin-coated sand]

[0031] The resin composition of the present embodiment is used as a binder for resin-coated sand, and contains a lignin-modified novolac-type phenolic resin. The content of free phenols contained in the lignin-modified novolac-type phenolic resin used in the resin composition of the present embodiment is less than 2% by mass. By using this lignin-modified novolac-type phenolic resin, the cured product of the resin composition containing the resin has excellent mechanical strength and low expansion. In addition, the resin composition containing this lignin-modified novolac-type phenolic resin has almost no or reduced generation of tar and smoke. Therefore, the casting mold manufactured by the resin-coated sand obtained by using this resin composition as a binder has high casting strength and reduces the generation of tar or smoke. Below, the components used in the resin composition of the present embodiment are described.

[0032] (Lignin modified novolac type phenolic resin)

[0033] In the lignin-modified novolac phenolic resin used in the resin composition of the present embodiment, the content of free phenols is 2% by mass or less. Here, the free phenols contained in the lignin-modified novolac phenolic resin refer to phenols that remain in an unreacted state and are used as a raw material component for manufacturing the lignin-modified novolac phenolic resin. By using a lignin-modified novolac phenolic resin having such a free phenol content, the obtained resin composition has mechanical strength and expansion properties suitable for use as a binder for resin-coated sand.

[0034] The lignin-modified novolac-type phenolic resin used in the resin composition of the present embodiment is a novolac-type phenolic resin obtained by reacting lignin, phenols, and aldehydes in the presence of an acid catalyst.

[0035] The number average molecular weight of the lignin-modified novolac phenolic resin used in the resin composition of the present embodiment is, for example, 200 to 1,500, preferably 400 to 1,200, and more preferably 500 to 1,000. By using a lignin-modified novolac phenolic resin having a number average molecular weight within the above range, the cured product of the obtained resin composition has improved mechanical strength.

[0036] The lignin modification rate of the lignin-modified novolac-type phenol resin used in the resin composition of the present embodiment is preferably 10% to 50%, and more preferably 14% to 50%.

[0037] The lignin-modified novolac-type phenolic resin used in the resin composition of the present embodiment preferably has a softening point of 70° C. to 105° C., and more preferably has a softening point of 75° C. to 95° C. By using a lignin-modified novolac-type phenolic resin having a softening point in such a relatively low temperature range, the cured product of the obtained resin composition has high mechanical strength.

[0038] (Method for producing lignin-modified novolac-type phenolic resin)

[0039] The lignin-modified novolac-type phenolic resin containing a predetermined amount of free phenols used in the resin composition of the present embodiment is preferably prepared by reacting lignin, phenols and aldehydes in the presence of an acid catalyst. The lignin-modified novolac-type phenolic resin used in the present embodiment has the above-mentioned desired physical properties by adjusting the manufacturing conditions. Hereinafter, the materials and manufacturing conditions for the lignin-modified novolac-type phenolic resin used in the resin composition of the present embodiment are described in detail.

[0040] <Phenols>

[0041] As phenols used to produce the lignin-modified novolac-type phenolic resin used in the present embodiment, phenol, phenol derivatives, and combinations thereof can be cited. As phenol derivatives, phenol having any substituent introduced into the benzene ring can be used. As substituents, hydroxyl groups; lower alkyl groups such as methyl and ethyl groups; halogen atoms such as fluorine, chlorine, bromine, and iodine; amino groups; nitro groups; carboxyl groups, etc. can be cited. Specific examples of phenols that can be used include phenol, catechol, resorcinol, hydroquinone, o-cresol, m-cresol, p-cresol, o-fluorophenol, m-fluorophenol, p-fluorophenol, o-chlorophenol, m-chlorophenol, p-chlorophenol, o-bromophenol, m-bromophenol, p-bromophenol, o-iodophenol, m-iodophenol, p-iodophenol, o-aminophenol, m-aminophenol, p-aminophenol, o-nitrophenol, m-nitrophenol, p-nitrophenol, 2,4-dinitrophenol, 2,4,6-trinitrophenol, salicylic acid, p-hydroxybenzoic acid, and combinations thereof. Phenols may be used alone or in combination of two or more.

[0042] As phenols, alkylphenols having 2 to 18 carbon atoms can also be used. Alkylphenols may have a branched chain on the alkyl chain or may have an unsaturated bond. In addition, the substitution position of the alkyl chain on the benzene ring may be any of ortho, meta, and para substitutions. Examples of alkylphenols include ethylphenol, n-propylphenol, isopropylphenol, n-butylphenol, sec-butylphenol, tert-butylphenol, pentylphenol, tert-aminophenol, hexylphenol, heptylphenol, octylphenol, tert-octylphenol, nonylphenol, tert-nonylphenol, decylphenol, undecylphenol, dodecylphenol, tridecylphenol, tetradecylphenol, pentadecylphenol, cardanol, cardol, urushiol, hexadecylphenol, methyl cardol, heptadecylphenol, laccol, burian urushiol, and octadecylphenol. As the alkylphenols, plant oils such as cashew nut shell liquid (cashew nut oil) and Rhus verniciflua extract can be used.

[0043] Among them, as the phenol, it is preferred to use at least one selected from phenol, cresol, xylenol, alkylphenol and bisphenol. From the viewpoint of production cost, it is preferred to use phenol, cresol, butylphenol and bisphenol A.

[0044] <Lignin>

[0045] The lignins used for producing the lignin-modified novolac-type phenolic resin used in the present embodiment include at least one selected from lignin and lignin derivatives.

[0046] Lignin is the main component that forms the structure of plants together with cellulose and hemicellulose, and is one of the most abundant aromatic compounds in nature. Lignin exists in the form of lignocellulose in part of the plant by bonding, so lignin generally refers to lignin obtained from plants by decomposition, etc., and examples thereof include: pulp lignin such as kraft lignin, lignin sulfonic acid, soda lignin, soda-anthraquinone lignin; organic solvent lignin; lignin phenol added with phenol when extracting with concentrated sulfuric acid in high-temperature and high-pressure water-treated lignin or blasted lignin; phenolated lignin, etc. The source of lignin is not particularly limited, and examples thereof include wood or herbs that contain lignin to form a woody part, such as conifers such as fir, pine, cypress, and cypress; broad-leaved trees such as beech, birch, oak, beech, and eucalyptus; and grasses (herbs) such as rice, wheat, corn, and bamboo.

[0047] In this embodiment, "lignin derivative" refers to a compound having a unit structure constituting lignin or a structure similar to a unit structure constituting lignin. Lignin derivatives have a phenol derivative as a unit structure. Since the unit structure has a chemically and biologically stable carbon-carbon bond or carbon-oxygen-carbon bond, it is not easy to chemically degrade and biodegrade.

[0048] As lignin derivatives, guaiacylpropane (ferulic acid) represented by formula (A) of the following formula (1), syringylpropane (erulic acid) represented by formula (B) and 4-hydroxyphenylpropane (coumaric acid) represented by formula (C) can be cited. The composition of lignin derivatives varies depending on the biomass used as the raw material. Lignin derivatives containing a guaiacylpropane structure are mainly extracted from coniferous trees. Lignin derivatives containing a guaiacylpropane structure and a syringylpropane structure are mainly extracted from broad-leaved trees. Lignin derivatives containing a guaiacylpropane structure, a syringylpropane structure and a 4-hydroxyphenylpropane structure are mainly extracted from herbs.

[0049]

[0050] Lignin derivatives are preferably obtained by decomposing biomass. Biomass is a substance that takes in carbon dioxide in the atmosphere during photosynthesis and fixes it, so biomass helps to suppress the increase of carbon dioxide in the atmosphere. By using biomass in industry, it can help to suppress the global warming effect. As biomass, lignocellulosic biomass can be cited. As lignocellulosic biomass, leaves, bark, branches and wood of plants containing lignin and their processed products can be cited. As plants containing lignin, the above-mentioned broad-leaved trees, coniferous trees, herbs, etc. can be cited.

[0051] As a method for decomposing biomass, there can be cited a method for chemical treatment, a method for hydrolysis treatment, a steam explosion method, a supercritical water treatment method, a subcritical water treatment method, a mechanical treatment method, a sulfuric acid cresol method, a pulp manufacturing method, and the like. From the perspective of environmental load, steam explosion, subcritical water treatment, and a mechanical treatment method are preferred. From the perspective of cost, a pulp manufacturing method is preferred. In addition, from the perspective of cost, it is preferred to use by-products of biomass utilization. Lignin derivatives can be prepared, for example, by decomposing biomass under the conditions of 150 to 400° C., 1 to 40 MPa, and 8 hours or less in the presence of various cooking liquids or solvents. In addition, lignin derivatives can be prepared by the methods disclosed in Japanese Patent Publication No. 2009-084320 and Japanese Patent Publication No. 2012-201828.

[0052] As lignin derivatives, materials obtained by decomposing lignocellulose formed by combining lignin, cellulose and hemicellulose can be cited. Lignin derivatives can include lignin decomposition products, cellulose decomposition products and hemicellulose decomposition products, etc., which are mainly composed of compounds having a lignin skeleton. In addition, lignin derivatives can also include inorganic substances from biomass sources or process sources, but in the case of the use of the present embodiment, the content of inorganic substances is preferably less than 10% by mass relative to the overall lignin derivative used.

[0053] The lignin derivative preferably has a plurality of reaction sites that allow the curing agent to act by electrophilic substitution reaction on the aromatic ring. From the viewpoint of excellent reactivity when the steric hindrance near the reaction site is small, at least one of the ortho and para positions of the aromatic ring containing the phenolic hydroxyl group is preferably unsubstituted, and the lignin of coniferous trees or grasses having a structure containing a plurality of guaiacyl cores or 4-hydroxyphenyl cores as the aromatic unit of the lignin is preferably used. As the lignin derivative, the substances disclosed in Japanese Patent Publication No. 2009-084320 and Japanese Patent Publication No. 2012-201828 can be used.

[0054] Furthermore, the lignin derivative may be a substance having a functional group on the lignin derivative in addition to the above-mentioned basic structure (lignin secondary derivative).

[0055] As the functional group possessed by the secondary derivative of lignin, there is no particular limitation, for example, preferably two or more identical functional groups can react with each other or can react with other functional groups. Specifically, in addition to epoxy and methylol, vinyl, acetylene, maleimide, cyanate, isocyanate, etc. with carbon-carbon unsaturated bonds can also be cited. Among them, it is preferred to use a lignin derivative (methylolated) into which methylol is introduced. This secondary derivative of lignin is self-crosslinked by the self-condensation reaction of methylol, and is crosslinked with the alkoxymethyl or hydroxyl in the following crosslinking agent. As a result, a lignin-modified novolac type phenolic resin with a particularly homogeneous and rigid skeleton and excellent solvent resistance is obtained.

[0056] Moreover, the lignin derivative used in the present embodiment may have a carboxyl group. Lignin obtained by pulping process or high temperature and high pressure water treatment sometimes has a carboxyl group. The lignin modified novolac type phenolic resin obtained by the lignin derivative having a carboxyl group has a plurality of crosslinking points with the curing agent described below, so that the crosslinking density of the obtained crosslinked body can be increased, and as a result, a crosslinked body with excellent solvent resistance can be obtained.

[0057] Among them, in the case where the above-mentioned lignin derivative has a carboxyl group, when assigning the carboxyl group 13In C-NMR analysis, the carboxyl group can be confirmed by the presence or absence of absorption of a peak at 172 to 174 ppm.

[0058] The weight average molecular weight of the lignin used to manufacture the lignin-modified novolac-type phenolic resin used in the present embodiment is, for example, 2,000 or more and 100,000 or less. The lower limit of the weight average molecular weight is preferably 2,500 or more, more preferably 3,000 or more, and further preferably 4,000 or more. The upper limit of the weight average molecular weight is preferably 90,000 or less, more preferably 80,000 or less, and further preferably 75,000 or less. The resin composition containing the lignin-modified novolac-type phenolic resin obtained by using the lignin with a weight average molecular weight in the above range is excellent in curability, and its cured product has high mechanical strength and low expansion. The weight average molecular weight is the weight average molecular weight converted to polystyrene measured by gel permeation chromatography, which can be obtained by the method of the embodiment.

[0059] The number average molecular weight of the lignin used to manufacture the lignin-modified novolac-type phenolic resin used in the present embodiment is, for example, 200 or more and 5,000 or less. The lower limit of the number average molecular weight is preferably 300 or more, more preferably 350 or more, and further preferably 400 or more. The upper limit of the number average molecular weight is preferably 4,000 or less, more preferably 3,000 or less, and further preferably 2,000 or less. The lignin with the number average molecular weight in the above range is excellent in reactivity, and thus the operability in the manufacturing process of the lignin-modified novolac-type phenolic resin is excellent, so it is preferred. In addition, by using the lignin with the number average molecular weight in the above range, the obtained lignin-modified novolac-type phenolic resin has excellent curing properties, and its cured product has high mechanical strength. The number average molecular weight is the number average molecular weight converted to polystyrene measured by gel permeation chromatography, which can be obtained by the method of the embodiment.

[0060] Here, an example of the method for measuring the molecular weight by the above-mentioned gel permeation chromatography is described.

[0061] In the method of measuring molecular weight by gel permeation chromatography, first, lignin derivatives are dissolved in a solvent to prepare a measurement sample. As long as the solvent used at this time can dissolve the lignin derivative, there is no particular limitation. From the perspective of the measurement accuracy of gel permeation chromatography, for example, tetrahydrofuran and N-methyl-2-pyrrolidone are preferred. The lignin used in the manufacture of the lignin-modified novolac phenolic resin used in the present embodiment may contain insoluble components formed by biomass, inorganic substances from process sources, and high molecular weight organic substances from plant sources, so the molecular weight of the lignin is obtained by selecting an appropriate solvent and filtering the insoluble components. In addition, in order to improve the lignin modification rate of the obtained lignin-modified novolac phenolic resin, the insoluble components of the lignin used are preferably less than 30% by mass in an appropriate solvent. In addition, the molecular weight of the lignin-modified novolac phenolic resin is also obtained by filtering the insoluble components. The content of the insoluble components in the lignin-modified novolac phenolic resin is preferably less than 15% by mass, more preferably less than 10% by mass. When the content is within the above range, the lignin-modified novolac-type phenolic resin has good curability, and can be cured uniformly in particular.

[0062] Next, organic general purpose columns "TSKgel SuperAW4000 (manufactured by Tosoh Corporation)", "TSKgel SuperAW3000 (manufactured by Tosoh Corporation), "TSKgelSuperAW2500 (manufactured by Tosoh Corporation)" and "TSKgel SuperAW2500 (manufactured by Tosoh Corporation)" filled with a styrene-based polymer filler are connected in series to a GPC system "HLC-8420GPC EcoSEC Elite (manufactured by Tosoh Corporation)". 30 μL of the above-mentioned measurement sample is injected into the GPC system, and N-methyl-2-pyrrolidone as an eluent is developed at 0.3 mL / min under the condition of 40°C, and the retention time is measured using the differential refractive index (RI) and ultraviolet absorbance (UV). The number average molecular weight and weight average molecular weight of the object can be calculated based on a calibration curve separately prepared to show the relationship between the retention time and the molecular weight of a standard polystyrene. As a detection mode, the refractive index is preferably used.

[0063] In addition, the organic general columns "TSKgelGMHXL (manufactured by Tosoh Corporation)" and "G2000HXL (manufactured by Tosoh Corporation)" filled with styrene-based polymer fillers are connected in series with the GPC system "HLC-8320GPC (Tosoh Corporation)". 200 μL of the above-mentioned measurement sample is injected into the GPC system, and the tetrahydrofuran of the eluent is developed at 1.0 mL / min at 40°C, and the retention time is measured using the differential refractive index (RI) and ultraviolet absorbance (UV). According to the calibration curve separately prepared to show the relationship between the retention time and the molecular weight of the standard polystyrene, the number average molecular weight and the weight average molecular weight of the object can be calculated. As a detection mode, the refractive index is preferred.

[0064] The molecular weight of the standard polystyrene used for preparing the calibration curve is not particularly limited, and for example, standard polystyrene (manufactured by Tosoh Corporation) having a weight average molecular weight of 2,110,000, 1,090,000, 427,000, 190,000, 37,900, 18,100, 5,970, 2,420, and 500 can be used.

[0065] The type and properties of the lignin used for producing the lignin-modified novolac-type phenolic resin of the present embodiment are not particularly limited, and for example, lignin having a softening point of 80° C. or higher can be used. Such lignin is preferred because of its good handling and processability.

[0066] The softening point of lignin can be measured using a ring and ball softening point tester (e.g., ASP-MG2 manufactured by MELTEC Corporation) in accordance with JIS K2207. In addition, when lignin contains a large amount of water, the sample is measured after being absolutely dried at 70° C. or below. In the present embodiment, for example, when a good sample cannot be prepared using a hot plate at 150 to 200° C. due to the thermal melting property of lignin, it is judged that the softening point is high and cannot be measured.

[0067] The volatile components of lignin are preferably 60% by mass or less, more preferably 50% by mass or less, and further preferably 40% by mass or less. When the volatile components of lignin are within the above range, the reactivity of lignin can be increased, thereby increasing the reactivity of the obtained lignin-modified novolac-type phenolic resin. The main volatile component is usually water, which can be calculated by, for example, spreading 4 g in an aluminum cup and drying it at 80° C. for 20 hours.

[0068] When using lignin obtained by decomposing biomass, sometimes a large amount of low molecular weight components are mixed in, which sometimes cause volatile components and odors during heating and a decrease in softening point. These components can be used directly or removed by heating, drying, etc. of lignin to adjust the softening point and odor.

[0069] <Aldehydes>

[0070] As the aldehydes for manufacturing the lignin modified novolac type phenolic resin used in the present embodiment, formaldehyde, paraformaldehyde, trioxane, acetaldehyde, propionaldehyde, polyoxymethylene, chloral, hexamethylenetetramine, furfural, glyoxal, n-butyraldehyde, hexanal, allyl aldehyde, benzaldehyde, crotonaldehyde, acrolein, tetraformaldehyde, phenylacetaldehyde, o-tolualdehyde, salicylaldehyde, p-xylene dimethyl ether etc. can be enumerated. Preferably formaldehyde, paraformaldehyde, trioxane, polyoxymethylene, acetaldehyde, p-xylene dimethyl ether and their combination etc. are enumerated. Aldehydes can be used alone or in combination of more than two kinds. Among these, from the viewpoint of productivity and cheapness, preferably formaldehyde or acetaldehyde are used.

[0071] <Acid Catalyst>

[0072] As the acid catalyst for manufacturing the lignin modified novolac type phenolic resin used in the present embodiment, any substance that can be used as a reaction catalyst can be used, and organic acid, inorganic acid and their combination can be used. As the organic acid, acetic acid, formic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, benzoic acid, salicylic acid, sulfonic acid, phenolsulfonic acid, p-toluenesulfonic acid, etc. can be mentioned. As the inorganic acid, hydrochloric acid, sulfuric acid, sulfate, phosphoric acid, phosphate, etc. can be mentioned.

[0073] When manufacturing the lignin modified novolac type phenolic resin used in the present embodiment, the molar ratio (F / P) of aldehydes to phenols is, for example, 0.4 or more, preferably 0.45 or more, and more preferably 0.5 or more. The upper limit of the molar ratio (F / P) of aldehydes to phenols is, for example, 1.0 or less, preferably 0.9 or less, and more preferably 0.85 or less. By reacting under the condition that the molar ratio (F / P) of aldehydes to phenols is within the above range, a lignin modified novolac type phenolic resin having the above characteristics, improved mechanical strength after curing and low expansion can be obtained.

[0074] When manufacturing the lignin-modified novolac-type phenolic resin of the present embodiment, the process of reacting lignin, phenols and aldehydes in the presence of an acid catalyst may include: mixing lignin and phenols under heating at 70°C to 120°C to disperse the lignin to obtain a mixture (process 1); mixing the acid catalyst simultaneously with process 1 or after process 1 (process 2); and mixing aldehydes after process 2. In addition, the process of reacting lignin, phenols and aldehydes in the presence of an acid catalyst is preferably carried out at a temperature of 60°C to 120°C, preferably at a temperature of 80°C to 105°C, for a reaction time of, for example, 10 minutes to 100 minutes. Thus, the reaction can be carried out efficiently and fully. In addition, by carrying out the process under heating, the starting materials are uniformly mixed, and the obtained lignin-modified novolac-type phenolic resin is uniformly cured by entanglement between molecules or action between molecules, so that molding with excellent dimensional accuracy can be achieved. The reaction time is not particularly limited and may be appropriately determined depending on the type of starting materials, the blending molar ratio, the amount and type of the catalyst used, and the reaction conditions.

[0075] The above-mentioned steps 1, 2 and 3 are preferably carried out under solvent-free conditions, but an organic solvent or water can also be used as a solvent. Instead of adding water, water-containing lignin can also be used. As organic solvents, for example, alcohols, ketones, esters, ethers, and hydrocarbons can be mentioned. As alcohols, methanol, ethanol, n-propanol, isopropanol, butanol, amyl alcohol, hexanol, octanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, glycerol, etc. can be mentioned. As ketones, acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, etc. can be mentioned. As esters, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methoxybutyl acetate, amyl acetate, methyl lactate, ethyl lactate, butyl lactate, etc. can be mentioned. As ethers, propyl ether, dioxane, methyl cellosolve, ethyl cellosolve, propyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl carbitol, ethyl carbitol, butyl carbitol, methyl cellosolve acetate, ethyl cellosolve acetate, propyl cellosolve acetate, butyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate can be mentioned. As hydrocarbons, toluene, xylene, pentane, hexane, cyclohexane, heptane, octane, decane, solvent naphtha, industrial gasoline, petroleum ether, petroleum spirit, solvent gasoline, etc. can be mentioned. They can be used alone or in combination of two or more.

[0076] Here, in the conventional method of increasing the molecular weight of the lignin-modified novolac-type phenolic resin by adjusting the reaction ratio of phenols, lignins and aldehydes, the viscosity of the reactants increases and dehydration becomes difficult, so the process time is sometimes prolonged. In addition, a large amount of unreacted phenols may remain.

[0077] In contrast, in the present embodiment, compared with the existing case of increasing the molecular weight by the reaction ratio of phenols, lignins and aldehydes, the process time can be shortened and the yield of the resin can be increased. Furthermore, by setting the molar ratio (F / P) of aldehydes to phenols within the above range and adjusting the molecular weight, molecular weight distribution and addition amount of the lignin used, the properties of the obtained lignin-modified novolac type phenolic resin and the physical properties of the resin material can be adjusted within the desired range. Furthermore, by using the above conditions, the unreacted free phenols contained in the obtained lignin-modified novolac type phenolic resin can be reduced to an amount of less than 2% by mass relative to the lignin-modified novolac type phenolic resin.

[0078] The lignin-modified novolac-type phenolic resin obtained by the above method preferably has a number average molecular weight of 200 to 1,500, more preferably 400 to 1,200, and even more preferably 500 to 1,000. The lignin-modified novolac-type phenolic resin having a number average molecular weight within the above range has excellent mechanical strength suitable for use as a binder for resin-coated sand, and has low expansion.

[0079] The lignin-modified novolac-type phenolic resin obtained by the above method preferably has a softening point of 70° C. to 105° C., and more preferably has a softening point of 75° C. to 95° C.

[0080] (Lubricant)

[0081] The resin composition of the present embodiment may contain a lubricant. By using a lubricant, the strength and adhesion resistance of the mold made of the resin coated sand can be improved. As a lubricant, for example, amide compounds such as ethylene bis stearamide, ethylene bis oleamide, methylene bis stearamide, oxystearamide, stearamide, palmitamide, oleamide, and hydroxymethylamide are preferably used. And, as other usable lubricants, calcium stearate, polyethylene wax, paraffin, montan wax, carnauba wax, etc. can be cited. They can be used alone or in combination of two or more.

[0082] The amount of lubricant used is preferably 0.3 to 5 parts by mass relative to 100 parts by mass of lignin-modified novolac-type phenolic resin. When it is less than 0.3 parts by mass, the effect of improving strength and blocking resistance is small; when it exceeds 5 parts by mass, the curing speed slows down, hindering the adhesion between aggregates (sand), so it is not preferred. The method of formulating the lubricant is not particularly limited, and it is preferably added in a molten state after the reaction, or added in a mixer at a temperature of 70°C or above. In addition, the mixing time after addition is not particularly limited, and it is preferably mixed for more than 5 minutes. In addition, the lubricant can also be mixed with solid resin. In addition, the lubricant can also be added after the resin composition is manufactured, when the resin composition (binder) is mixed with aggregate (sand) to manufacture resin-coated sand.

[0083] (Silane coupling agent)

[0084] The resin composition of the present embodiment may contain a silane coupling agent. By using a silane coupling agent, the strength and adhesion resistance of the mold made of resin-coated sand can be improved. As a silane coupling agent, for example, aminosilane coupling agents such as N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, and γ-aminopropyltriethoxysilane can be used. Relative to 100 parts by mass of lignin-modified phenolic varnish type phenolic resin, the amount of silane coupling agent is preferably 0.05 to 5 parts by mass. By using it in such a range of amounts, the effect of improving the strength and adhesion resistance of the mold can be obtained. The method of mixing the silane coupling agent is not particularly limited, and it is preferably added in a molten state after the reaction, or added in a mixer at a temperature of 70°C or above. In addition, the mixing time after addition is not particularly limited, and it is preferably mixed for more than 5 minutes. Furthermore, the silane coupling agent may be added after the resin composition is produced, when the resin composition (binder) and aggregate (sand) are kneaded to produce resin-coated sand.

[0085] (Method for producing resin composition)

[0086] The resin composition of the present embodiment can be produced by kneading and stirring predetermined amounts of the above-mentioned components by a known method.

[0087] [Resin coated sand]

[0088] The resin-coated sand according to the present embodiment is composed of aggregates and a resin layer coating the aggregates, and the resin layer is formed from the resin composition according to the present embodiment described above.

[0089] (Manufacturing method of resin coated sand)

[0090] The method for producing the resin coated sand is not particularly limited. For example, a resin composition is first produced according to the above method, and then the aggregate and the resin composition are heated and mixed.

[0091] As the aggregate, a refractory granular material is used, for example, silica sand, chromite sand, zircon sand, olivine sand, mullite sand, synthetic mullite sand, magnesium oxide, alumina-based artificial sand, sun pearl sand, and their recovered sand, regenerated sand, etc., which are mainly composed of quartz, can be cited. In addition, the particle size distribution and particle diameter of the refractory granular material can be selected without particular limitation as long as it has refractory properties that can withstand casting and is suitable for mold formation.

[0092] Specifically, for example, the aggregate is first heated as the heating mixing. The heating temperature is appropriately set according to the type of the aggregate, and is, for example, 100° C. or higher, preferably 110° C. or higher, and, for example, 200° C. or lower, preferably 170° C. or lower.

[0093] Next, the heated aggregate and the lignin-modified novolac-type phenolic resin are mixed and stirred at a predetermined ratio, and a curing agent, a curing accelerator, a lubricant, and a silane coupling agent are further added as needed, and the mixture is kneaded and stirred while cooling until the aggregate blocks are broken down into particles. Thereafter, a lubricant is added as needed, and the mixture is further kneaded and stirred.

[0094] Thus, the aggregate is coated with the lignin-modified novolac-type phenolic resin, thereby obtaining resin-coated sand.

[0095] The resin-coated sand obtained by the above method includes a resin layer formed by a resin composition containing a lignin-modified novolac-type phenolic resin. Such resin-coated sand has high mechanical strength and low expansion. Therefore, the resin-coated sand of this embodiment is suitable for use as a casting material.

[0096] When resin coated sand is used as a casting material, the resin coated sand is filled into a molding die by a known method such as a gravity drop method or a blowing method, and after the resin coated sand is cured by heating, it is taken out from the molding die.

[0097] The heating conditions are, for example, 200° C. or more, preferably 250° C. or more, for example, 350° C. or less, preferably 300° C. or less. The heating time is, for example, 30 seconds or more, preferably 1 minute or more, for example, 5 minutes or less, preferably 3 minutes or less. Thus, a casting mold such as a sand core casting mold can be obtained in the form of a solidified product.

[0098] In addition, the use of the resin-coated sand is not limited to the above-mentioned use, and it can be used in various industrial fields.

[0099] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted.

[0100] Example

[0101] Hereinafter, the present invention will be described with reference to Examples and Comparative Examples, but the present invention is not limited thereto.

[0102] [Preparation of phenolic resin]

[0103] (Preparation Example 1)

[0104] The lignin-modified novolac-type phenolic resin 1 was produced by the following method.

[0105] (Preparation of lignin derivatives)

[0106] First, a lignin derivative for synthesizing a lignin-modified novolac-type phenolic resin was prepared according to the following steps.

[0107] For 1500 parts by weight of cedar wood powder with a moisture content of 50%, 5000 parts by weight of pure water as a cooking liquid, 180 parts by weight of sodium hydroxide, 120 parts by weight of sodium carbonate, and 7.5 parts by weight of 9,10-anthraquinone as a cooking aid were placed in a 10L stainless steel autoclave, and a cooking reaction was carried out at 170°C for 3 hours under stirring. The cooking liquid after the reaction was cooled to room temperature, and the pulp component was removed with a filter, and the black liquor containing lignin was separated. Dilute sulfuric acid was added to the separated black liquor to adjust the pH to 8, and the resulting precipitate was centrifuged. After washing twice with 500 parts by weight of water, the precipitate was suspended in 5 times the amount of water and readjusted to pH 2 with dilute sulfuric acid. The precipitated lignin was centrifuged again, washed with water, filtered by suction, spread on a large barrel for air drying, and dried in a reduced pressure oven at 70°C or below to obtain 140 to 150 parts by weight of brown powdery alkali lignin with a solid content of more than 70% (solid content conversion). The solid content of lignin was calculated from the residual content after 4 g of a sample was placed in an aluminum cup and heated and dried at 135° C. for 1 hour. The number average molecular weight (Mn) of the obtained lignin derivative was 2,000, and the weight average molecular weight (Mw) was 14,000.

[0108] (Preparation of lignin modified novolac type phenolic resin)

[0109] Then, the lignin-modified novolac-type phenolic resin 1 was synthesized according to the following steps.

[0110] 100 parts by weight of phenol was added to a four-necked flask equipped with a stirrer, a cooling tube and a thermometer, 15.8 parts by weight of the above-mentioned lignin derivative (solid content) was slowly added, and the mixture was dispersed by mixing at 60° C. or above, 1.3 parts by weight of oxalic acid was added, and 43.1 parts by weight of a 37% formaldehyde aqueous solution was slowly added over 60 minutes to react at 100° C. After the addition, the mixture was reacted at 100° C. for 60 minutes, and the mixture was heated to 150° C. or above under normal pressure and reduced pressure for dehydration. The mixture was taken out when the desired phenol concentration was reached, thereby obtaining 94.5 parts by weight of a lignin-modified novolac-type phenolic resin 1.

[0111] (Preparation Example 2)

[0112] The lignin-modified novolac-type phenol resin 2 was produced by the following method.

[0113] (Preparation of lignin derivatives)

[0114] For 200 parts by weight of cedar wood powder with a moisture content of 50%, 567 parts by weight of pure water as a cooking liquid were placed in a 10L stainless steel autoclave and treated at 300°C for 1 hour under stirring. The cooking liquid after the reaction was cooled to room temperature and filtered to obtain a solid component containing lignin. The obtained amount of solid components was immersed in 250 parts of acetone for 12 hours. It was filtered, acetone was distilled off from the filtrate at below 70°C and dried to obtain 15.2 parts by weight of lignin derivatives. The number average molecular weight (Mn) of the obtained lignin derivative was 580, and the weight average molecular weight (Mw) was 2,510.

[0115] (Preparation of lignin modified novolac type phenolic resin)

[0116] Next, 120.3 parts by weight of lignin-modified novolac-type phenol resin 2 was obtained in the same manner as in Preparation Example 1 except that 41.7 parts by weight (solid content) of the above-mentioned lignin derivative and 49.2 parts by weight of a 37% formaldehyde aqueous solution were used.

[0117] (Preparation Example 3)

[0118] The lignin-modified novolac-type phenolic resin 3 was produced according to the following method.

[0119] (Preparation of lignin derivatives)

[0120] A lignin derivative was obtained in the same manner as in Preparation Example 1 except that 5000 parts by weight of pure water, 150 parts by weight of sodium hydroxide, 80 parts by weight of sodium sulfide, 70 parts by weight of sodium carbonate and 7.5 parts by weight of 9,10-anthraquinone as a cooking aid were used as a cooking liquid, a cooking reaction was carried out at 170° C. for 2 hours, and the mixture was dried at 100° C. or less. The obtained lignin derivative had a number average molecular weight (Mn) of 1,920 and a weight average molecular weight (Mw) of 15,100.

[0121] (Preparation of lignin modified novolac type phenolic resin)

[0122] Next, 94.1 parts by weight of lignin-modified novolac-type phenol resin 3 was obtained in the same manner as in Preparation Example 1 except that 13.9 parts by weight (solid content) of the above-mentioned lignin derivative and 91.4 parts by weight of a 37% formaldehyde aqueous solution were used.

[0123] (Preparation Example 4)

[0124] The lignin-modified novolac-type phenolic resin 4 was produced according to the following method.

[0125] (Preparation of lignin derivatives)

[0126] In the same manner as in Preparation Example 1, a lignin derivative was obtained.

[0127] (Preparation of lignin modified novolac type phenolic resin)

[0128] Next, 98.2 parts by weight of lignin-modified novolac-type phenol resin 4 was obtained in the same manner as in Preparation Example 1 except that 15.8 parts by weight (solid content) of the above-mentioned lignin derivative and 47.4 parts by weight of a 37% formaldehyde aqueous solution were used.

[0129] (Preparation Example 5)

[0130] As the cashew nut modified novolac type phenolic resin 5, PR-12686E manufactured by Sumitomo Bakelite Co., Ltd. was used.

[0131] (Preparation Example 6)

[0132] Unmodified novolac-type phenolic resin 6 was produced in the following manner.

[0133] (Preparation of unmodified novolac type phenolic resin)

[0134] 100 parts of phenol, 1 part of oxalic acid and 56.9 parts of 37% formalin (F / P=0.68) were slowly added to a four-necked flask equipped with a stirrer, a cooling tube and a thermometer over 60 minutes, and reacted at 100°C. After the addition, the mixture was reacted at 100°C for 60 minutes, and the temperature was raised to above 150°C under normal pressure and reduced pressure dehydration. When the desired phenol concentration was reached, the mixture was taken out to obtain 87.9 parts by weight of unmodified novolac type phenolic resin 6.

[0135] (Preparation Example 7)

[0136] The lignin-modified novolac-type phenolic resin 7 was produced by the following method.

[0137] (Preparation of lignin derivatives)

[0138] In the same manner as in Preparation Example 1, a lignin derivative was obtained.

[0139] (Preparation of lignin modified novolac type phenolic resin)

[0140] Next, 125.2 parts by weight of lignin-modified novolac-type phenol resin 7 was obtained in the same manner as in Preparation Example 1 except that 40.5 parts by weight (solid content) of the above-mentioned lignin derivative and 54.8 parts by weight of a 37% formaldehyde aqueous solution were used.

[0141] [Characteristics of phenolic resin]

[0142] The number average molecular weight, lignin modification rate, free phenol content and softening point of the phenolic resin obtained in the above preparation example were measured by GPC method or ring and ball softening point tester. These measurement results are shown in Table 1 as "properties of phenolic resin".

[0143] <Examples 1 to 3, Comparative Examples 1 to 5>

[0144] [Preparation of resin composition]

[0145] In Examples 1 to 3 and Comparative Examples 1 to 5, the components shown in Table 1 were mixed in predetermined amounts according to the following procedures to obtain resin compositions.

[0146] (Preparation of lignin-modified novolac-type phenolic resin composition)

[0147] In Examples 1 to 3 and Comparative Examples 1 to 4, 100 parts by weight of a phenolic resin, 1 part of ethylenebisstearamide, and 1 part of an aminosilane as a silane coupling agent were kneaded for 5 minutes using a roll kneader with the surface temperature adjusted to 70 to 90° C. to obtain a composition that is solid at room temperature. The obtained composition was pulverized and mixed with 0.2 parts by weight of stearic acid in a bag to obtain a phenolic resin composition.

[0148] In Comparative Example 5, 100 parts by weight of a phenolic resin and 0.2 parts by weight of stearic acid were mixed in the same manner as above to obtain a phenolic resin composition.

[0149] The detailed information of the components described in Table 1 is shown below.

[0150] (Phenolic resin)

[0151] Phenolic resin 1: Lignin-modified novolac-type phenolic resin 1 of Preparation Example 1

[0152] Phenolic resin 2: Lignin-modified novolac-type phenolic resin 2 of Preparation Example 2

[0153] Phenolic resin 3: Lignin-modified novolac-type phenolic resin 3 of Preparation Example 3

[0154] Phenolic resin 4: Lignin-modified novolac-type phenolic resin 4 of Preparation Example 4

[0155] Phenolic resin 5: cashew modified novolac type phenolic resin (Mw = 910, Mn = 26700)

[0156] Phenolic resin 6: Unmodified novolac type phenolic resin (Mw = 640, Mn = 1280)

[0157] Phenolic resin 7: Lignin-modified novolac-type phenolic resin 7 of Preparation Example 7

[0158] (Lubricant)

[0159] Lubricant 1: Ethylene bisstearamide

[0160] Lubricant 2: Calcium stearate

[0161] · Coupling agent 1: N-(2-aminoethyl)-3-aminopropyltrimethoxysilane

[0162] [Physical properties of resin composition]

[0163] The following physical properties were measured for the resin compositions obtained in the respective Examples and Comparative Examples.

[0164] (Amount of tar and smoke produced)

[0165] 100 parts by weight of the phenolic resin composition obtained in each example and comparative example and 15 parts by weight of urotropine were ground and mixed using a small grinder to obtain a thermosetting resin composition with a median particle size of about 30 μm. The composition was then cured at 150°C for 30 minutes and ground to obtain a cured product. Place 1.5 g of solidified material in a 30 mm high crucible (small), and cover with aluminum foil. A crucible (large) with a height of 55 mm was covered with a lid and heated at 430° C. for 30 minutes. After cooling, the weights of the crucible (large), aluminum foil and lid were measured, and the amount of tar and smoke generated by the resin composition due to the heat treatment was calculated according to the following formula.

[0166] Amount of tar and smoke generated (%) = {[(weight of aluminum foil after heating at 430°C (g) + weight of crucible (large) (g) + weight of lid (g)) - (weight of aluminum foil before heating at 430°C (g) + weight of crucible (large) (g) + weight of lid (g))] / weight of solidified product before heating (g)} × 100 (%)

[0167] [Preparation of resin coated sand]

[0168] 105 parts of the resin composition obtained in each example and comparative example and 7000 parts of aggregate (regenerated silica sand) heated to 130-140°C were put into an experimental vortex mixer and kneaded for 60 seconds. An aqueous solution obtained by dissolving 23 parts of a curing agent (hexamethylenetetramine) in 105 parts of water was added, and air cooling was performed, and then 7 parts of a lubricant (calcium stearate) was added to obtain resin coated sand (RCS).

[0169] [Physical properties of resin coated sand]

[0170] The following physical properties were measured for the obtained RCS.

[0171] (Cold flexural strength: bending strength)

[0172] The cold flexural strength was measured according to JACT test method SM-1. That is, using the obtained RCS, a JIS-type test piece (width: 10 mm × thickness: 10 mm × length: 60 mm) was prepared according to JIS-K-6910 (sintering conditions of the test object: 250°C, 60 seconds), and the bending strength (Kgf / cm 2 ).

[0173] (Coefficient of thermal expansion)

[0174] The thermal expansion coefficient was measured according to JACT test method SM-7. That is, using RCS, a test piece with a diameter × length of 30Φ × 50mm was prepared by firing at 250°C for 120 seconds, and the thermal expansion coefficient was measured in an atmosphere of 1000°C. The smaller the value, the lower the thermal expansion coefficient, and it can be expected that cracks during casting will be reduced.

[0175] (Welding point)

[0176] The melting point was measured according to JACT test method C-1 (melting point test method). That is, the RCS to be measured was quickly spread on a metal rod with a temperature gradient, and after 60 seconds, a nozzle with a diameter of 1.0 mm was moved along the guide rod at a distance of 10 cm from the above metal rod, and the RCS on the metal rod was blown away once with an air pressure of 0.1 MPa from the low temperature part to the high temperature part. The temperature of the boundary line between the blown away RCS and the unblown RCS was read to 1°C, and the melting point (°C) was calculated.

[0177]

[0178] The cured product of the resin composition of the example has high mechanical strength and generates less tar and smoke.

[0179] This application claims priority based on Japanese patent application No. 2022-079950, filed on May 16, 2022, the disclosure of which is incorporated herein in its entirety by reference.

Claims

1. A resin composition for resin coated sand, characterized in that: The resin composition contains a lignin-modified novolac-type phenolic resin. The content of free phenols in the lignin-modified novolac-type phenolic resin is 2% by mass or less.

2. The resin composition according to claim 1, characterized in that The lignin-modified novolac-type phenolic resin is a novolac-type phenolic resin obtained by reacting lignin, phenols, and aldehydes in the presence of an acid catalyst.

3. The resin composition according to claim 1 or 2, characterized in that The number average molecular weight of the lignin-modified novolac-type phenolic resin is 200 or more and 1500 or less.

4. The resin composition according to claim 2, characterized in that The weight average molecular weight of the lignin is 2,000 to 100,000.

5. The resin composition according to any one of claims 1 to 4, characterized in that The softening point of the lignin-modified novolac-type phenolic resin is 70° C. or higher and 105° C. or lower.

6. The resin composition according to any one of claims 1 to 5, characterized in that The lignin modification rate of the lignin-modified novolac-type phenolic resin is 10% to 50%.

7. The resin composition according to any one of claims 1 to 6, characterized in that Also contains lubricant.

8. The resin composition according to claim 7, characterized in that The lubricant includes an amide compound.

9. The resin composition according to any one of claims 1 to 8, characterized in that It also contains a silane coupling agent.

10. The resin composition according to claim 9, characterized in that The silane coupling agent includes an aminosilane coupling agent.

11. A resin coated sand, characterized in that: A resin composition comprising an aggregate, a lubricant and any one of claims 1 to 10.

12. The resin coated sand according to claim 11, characterized in that: Also contains a silane coupling agent.

13. The resin coated sand according to claim 11 or 12, characterized in that: The aggregate is coated with a resin layer formed from the resin composition.